Endometrial Immune Profiling: A Method to Design Personalized Care in Assisted Reproductive Medicine - Lédée, Nathalie; Petitbarat, Marie; Prat-Ellenberg, Laura; Dray, Géraldine; Cassuto, Guy N.; Chevrier, Lucie; Kazhalawi, Alaa; Vezmar, Katia; Chaouat, Gerard (Frontiers in Immunology, 2020)
Objective Evaluate the effectiveness of the endometrial immune profiling as a method to design personalized care in order to enhance the chance of pregnancy in a large population of infertile women including different clinical contexts. The hypothesis is that some failures could be the consequence of some uterine immune deregulations that could be corrected through personalized care. Design A prospective cohort study Setting Multicentric study Intervention(s) and Main outcome measure(s) 1738 infertile patients benefitted from an endometrial immune profiling between 2012 and 2018. The endometrial immune profiling documented the absence or the presence of endometrial immune deregulation and identified its type. If a deregulation was observed, suggestions of personalization were sent to the physician aiming at counteracting the disequilibrium observed. One year after the endometrial immune profiling, the physician is re-contacted to document the outcome of the first subsequent embryo transfer following the evaluation. Result(s) 16.5% of the infertile patients were diagnosed as having no immune deregulation, 28% had a low-immune profile of activation, 45% exhibit a local over-immune activation, 10.5 % had a mixed profile of immune activation. Pregnancy rates were significantly higher for patients with history of repeated implantation failures (RIF) or recurrent miscarriages (RM) after a well diagnosed deregulation and an applied personalized care, compared to non-deregulated patients (respectively 37.7% and 56% and versus 26.9 and 24%, p<0.001). In contrast, in good prognosis IVF (in vitro fertilization) /ICSI (intracytoplasmic sperm injection) subgroup and patients in oocytes donation, no difference was observed between deregulated versus not deregulated subgroups, but the highest pregnancy rates were observed in absence of deregulation. For patients with over-immune activation, pregnancy rates were significantly higher for patients who had a test of sensitivity regarding the type of immunotherapy introduced, as compared to the ones who did not (49% versus 36.39%, p=0.0012). Conclusion(s) Endometrial local immunity appears to be a new and important parameter able to influence the prognosis of pregnancy. Medical care of deregulation resulted in significant higher pregnancy rates in RIF and RM patients.